Kinect Development Kit: A Toolkit for Gesture- and Speech-Based Human-Machine Interaction - Tashev, Ivan (Signal Processing Magazine, 2013)
Kinect is a device for human-machine interaction, which adds two more input modalities to the palette of the user interface designer: gestures and speech. Kinect is transforming how people interact with computers, kiosks, and other motion-controlled devices from fun applications like playing a virtual violin, to applications in health care and physical therapy, retail, education, and training. The Kinect for Windows SDK and toolkit contain drivers, tools, APIs, device interfaces, and code samples to simplify development of applications with Kinect. The KDK has integrated skeletal and facial tracking and gesture recognition. Voice recognition adds an additional dimension of human comprehension, while Kinect Fusion reconstructs data into 3D models.